2005
DOI: 10.1177/0361198105192900124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Predicted Dynamic Modulus for Florida Mixtures

Abstract: The new 2002 AASHTO guide for the design of pavement structures is based on mechanistic principles and requires the dynamic modulus as input to compute stress, strain, and rutting and cracking damage in flexible pavements. The 2002 AASHTO guide has three different levels of analysis; the level used depends on the importance of the pavement structure in question. Dynamic modulus testing is required for Level 1 pavement analysis, whereas no laboratory test data are required for Level 2 and Level 3 pavement analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 2 publications
(6 reference statements)
1
16
0
Order By: Relevance
“…In addition, it is hypothesized that the Witczak equation may not be suitable for predicting |E * | of polymer-modified binders (Dongre et al, 2005). Birgisson, Sholar, and Roque (2005) examined the quality of Witczak model predictions for typical asphalt mixes in Florida. They found that Equation (3) can be used to predict measured |E * | values with the reliability of 85 to 90%, if the appropriate multiplier is used.…”
Section: The Hirsch Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is hypothesized that the Witczak equation may not be suitable for predicting |E * | of polymer-modified binders (Dongre et al, 2005). Birgisson, Sholar, and Roque (2005) examined the quality of Witczak model predictions for typical asphalt mixes in Florida. They found that Equation (3) can be used to predict measured |E * | values with the reliability of 85 to 90%, if the appropriate multiplier is used.…”
Section: The Hirsch Modelmentioning
confidence: 99%
“…On the other hand, a non-linear behaviour of asphalt mixture was detected at higher temperatures and/or lower frequencies, which is in contradiction to the trends observed in binders (Masad & Bahia, 2002). Similarly, Birgisson et al (2005) concluded that the response of asphalt mixture at high temperature (40 • C) is more dependent on the aggregate structure than it is at low temperature.…”
Section: Factors Influencing Measured |E * | Valuesmentioning
confidence: 99%
“…For use in the MEPDG, viscosity can be obtained in many ways: by using typical values embedded in the MEPDG based on performance grade or measured penetration, by using empirical relationships with conventional binder tests (ring and ball, penetration, softening point, or kinematic viscosity), by measuring Brookfield rotational viscosity or absolute viscosity, or by converting DSR G b * measured at 10 rad/s (6). Brookfield rotational viscosity is converted to viscosity at a desired temperature by determining regression parameters A and VTS from the relationship in the following equation: *, using recommended values for A and VTS, those predictions based on Brookfield rotational viscosity had the lowest bias and highest coefficient of determination (R 2 ) (11).…”
Section: Laboratory Testingmentioning
confidence: 99%
“…The |E*| of HMA depends on many mix factors: aggregate, binder, air voids, specimen size, etc. Many researchers developed empirical based |E*| models to address these factors and to predict the dynamic modulus of HMA [1][2][3][4][5][6][7][8][9][10]. These models try to predict the |E*| values using the aggregate gradation, viscosity, shear modulus, etc.…”
Section: Introductionmentioning
confidence: 99%